THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN ENSURING THE EMPLOYMENT OF THE POPULATION AND INCREASING THEIR INCOME (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
This scientific article emphasizes the role of small business and private entrepreneurship in providing employment and increasing income of the population, the service of representatives of this sector in the development of the country.